Lithium-assisted proton conduction at 150 degrees C in a microporous triazine-phenol polymer - Nandi, Shyamapada; Dhavale, Vishal M.; Shalini, Sorout; Werner-Zwanziger, Ulrike; Singh, Harpreet; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (Advanced Materials Interfaces, 2015)
Keywords: conduction; hydrophobic polar frameworks; lithiated polymers; proton conduction; triazine-phenol polymers

Low-overpotential electrocatalytic water splitting with noble-metal-free nanoparticles supported in a sp(3) n-rich flexible COF - Mullangi, Dinesh; Dhavale, Vishal M.; Shalini, Sorout; Nandi, Shyamapada; Collins, Sean; Woo, Tom; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2016)
Covalent organic frameworks (COFs) are crystalline organic polymers with tunable structures. Here, a COF is prepared using building units with highly flexible tetrahedral sp(3) nitrogens. This flexibility gives rise to structural changes which generate mesopores capable of confining very small (<2 nm sized) non-noble-metal-based nanoparticles (NPs). This nanocomposite shows exceptional activity toward the oxygen-evolution reaction from alkaline water with an overpotential of 258 mV at a current density of 10 mA cm(-2). The overpotential observed in the COF-nanoparticle system is the best in class, and is close to the current record of approximate to 200 mV for any noble-metalfree electrocatalytic water splitting system-the Fe-Co-Ni metal-oxide-film system. Also, it possesses outstanding kinetics (Tafel slope of 38.9 mV dec(-1)) for the reaction. The COF is able to stabilize such small-sized NP in the absence of any capping agent because of the COF-Ni(OH)(2) interactions arising from the N-rich backbone of the COF. Density-functional-theory modeling of the interaction between the hexagonal Ni(OH)(2) nanosheets and the COF shows that in the most favorable configuration the Ni(OH)(2) nanosheets are sandwiched between the sp(3) nitrogens of the adjacent COF layers and this can be crucial to maximizing their synergistic interactions.